Con GOCE per portare nello spazio un po' di Made in Europe (GEOmedia, 2008)
GOCE brings 'Made in Europe' to SpaceSurveyor's dream of an instrument capable of accurately measuring the Earth's gravimetry. Such a tool has been realised through the GOCE (Gravity field and steady-state Ocean Circulation Explorer). The ESA satellite ready to launch from Plesetsk russian cosmodrome was also realised. The launch already suffered a couple of delays due to problems with the launcher. ESA will be ready by the next available window to put the satellite in orbit which is the 27th of October.